2009
DOI: 10.1118/1.3085876
|View full text |Cite
|
Sign up to set email alerts
|

CZT detectors used in different irradiation geometries: Simulations and experimental results

Abstract: The purpose of this work was to evaluate potential advantages and limitations of CZT detectors used in surface-on, edge-on, and tilted angle irradiation geometries. Simulations and experimental investigations of the energy spectrum measured by a CZT detector have been performed using different irradiation geometries of the CZT. Experiments were performed using a CZT detector with 10 x 10 mm2 size and 3 mm thickness. The detector was irradiated with collimated photon beams from Am-241 (59.5 keV) and Co-57 (122 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Huruska et al [39] observed, measured and corrected this effect by combining a Monte Carlo-based method with an experimental setup for the pixelated CZT LumaGem 3200 S camera. Fritz and Shikhaliev [40] also recommended to reduce this effect in a planar CZT detector geometry by the use of tilted angle irradiation instead of normal incidence. It can be seen in figure 3 that crosstalk events of photon interaction in this region are essentially due to the contribution of septal penetration and scattered photons.…”
Section: Discussionmentioning
confidence: 99%
“…Huruska et al [39] observed, measured and corrected this effect by combining a Monte Carlo-based method with an experimental setup for the pixelated CZT LumaGem 3200 S camera. Fritz and Shikhaliev [40] also recommended to reduce this effect in a planar CZT detector geometry by the use of tilted angle irradiation instead of normal incidence. It can be seen in figure 3 that crosstalk events of photon interaction in this region are essentially due to the contribution of septal penetration and scattered photons.…”
Section: Discussionmentioning
confidence: 99%
“…The counts in the scatter window are therefore artificially exaggerated, leading to overestimation of scatter when using DEW scatter correction. Methods for correcting semiconductor detector tailing exist that would serve to improve overall counting statistics, but these modifications are not feasible in routine clinical practice. Our implementation of scatter and attenuation correction, however, aims to recover the true activity in a tumor relative to counts in‐air, which are subject to the same incomplete absorption; the overall accuracy is therefore unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…The tilted angle geometry was studied for linear array CdZnTe detectors for computed tomography (CT) applications to increase detector count rate (Shikhaliev 2006). The tilted angle irradiation of CdZnTe detector was also used for x-ray spectroscopy where it provided substantial improvement on low energy tailing of the energy spectrum due to hole trapping (Fritz and Shikhaliev 2009;Fritz et al 2011).…”
Section: Concept Of Tilted Angle Irradiationmentioning
confidence: 99%